Late-Pleistocene to Holocene sedimentary fills of the Cinarcik Basin of the Sea of Marmara - Eris, K. Kadir; Cagatay, Namik; Beck, Christian; de Lepinay, Bernard Mercier; Corina, Campos (Elsevier, 2012)
A giant RV Marion Dufresne piston core MD01-2425 recovered from the 1276 m-deep Cinarcik Basin of the Sea of Marmara documents characteristics of deep basin sedimentation influenced by large-scale gravity-controlled mass-wasting processes and associated turbidite deposition during the Late Pleistocene to Holocene. A visual lithological description of the core reveals twenty major seismoturbidite layers (>20 cm thick), intercalated in hemipelagic-type fine-grained calcareous and slightly siliceous clays. The thickness and frequency of the sesimoturbidite layers deposited during the lacustrine period (prior to 12.3 cal ka BP) is much greater than during the Holocene marine period. The sedimentary processes during deposition of seismoturbidites in the basin have been determined in this study using a combination of grain-size parameters. Often the seismoturbidites show strong grain segregation with a sharp boundary between a coarse lower and a homogeneous upper part. The traction carpet deposits formed at the base of a turbulent suspension and were produced in the lower coarse-grained part, whereas the homogeneous upper part was deposited by uniform suspensions following bedload deposition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Sea of Marmara; Seismic stratigraphy; Seismoturbidite; Mass-flow